Средства формирования социокультурной компетенции студентов-русистов в рамках занятий по практикуму русского языка - Kossakowska-Maras, Maria (Studia Rossica Posnaniensia, 2015)
This article discusses various ways of developing sociocultural competence in students who learn Russian as a foreign language. These ways of building up students’ sociocultural competence serve as sources of knowledge about the other culture. Two basic groups of factors that determine the development of sociocultural competence are shown, i.e. those that are present in the classroom and those that exist after classes. The author pays attention to students’ attitude toward the subject matter of what is taught, i.e. their independence, initiative as well as active participation in the teaching process.